(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
Catharanthus roseus is widely used in Indian Ayurvedic medicine for the treatment of diabetes mellitus. The present study was carried out to investigate the antidiabetic and hyperlipidemic potential of Catharanthus roseus on alloxan induced diabetes in male albino rats. Oral administration of aqueous extract of Catharanthus roseus at a dose of 250 mg, 350 mg, and 450 mg/kg body weight for 30 days to diabetic rats resulted in significant reduction in blood glucose, reduction in lipid profile and also prevented a decrease in body weight. Histological observation demonstrated significant fatty changes and inflammatory cell infiltrates in pancreas of diabetic rats. But, supplementation with Catharanthus roseus to diabetic rats significantly reduced the fatty changes and inflammatory cell infiltrates.